Protecting beaches and sea turtles: An analysis of beach nourishment in North Carolina, the impacts on nesting loggerhead sea turtles, and how sea level rise will transform the status quo. - Hernandez, Kimberly (2014)
Federally protected loggerhead sea turtles rely on wide sandy beaches for their terrestrial reproductive phase. Accustomed to hurricanes and erosion, North Carolina has taken to extensive beach nourishment efforts for shoreline protection. The majority of these efforts have been to benefit interests other than sea turtles, but given the recent critical habitat proposals for the Northwest Atlantic Ocean Distinct Population Segment of the Loggerhead Sea Turtle (Caretta caretta), submitted by the US Fish and Wildlife Service and the National Marine Fisheries Service in 2013, their consideration warrants further attention. Each beach selected for my study: 1) is a known loggerhead sea turtle nesting beach; 2) is within the proposed terrestrial critical habitat; 3) has a “High” to “Extremely High” vulnerability to sea level rise based on the US Geological Survey Coastal Vulnerability Index; and 4) is a developed barrier island. The final economic analysis was on Bogue Banks (Carteret County), Pleasure Island (New Hanover County), and Bald Head Island, Oak Island, and Holden Beach (Brunswick County). In this project, I explored historic nourishment data to understand the full costs of beach protection, hypothesizing that sea level rise will exacerbate that cost in the future. Through my research, I unveiled how nourishment efforts potentially both help and hinder the state and sea turtles. My analysis uncovered ways North Carolina can responsibly move forward with beach protection while taking both sea turtles and sea level rise into account. First, there must be state-level support for sea level rise planning – the Coastal Resources Commission should move forward with sea level rise discussions and define a rate of sea level change for planning purposes. This rate, and associated increased need for sand, should be incorporated into future nourishment projects so the US Army Corps of Engineers and the North Carolina Division of Coastal Management do not underestimate costs and how much sand will be needed over the ...